Shengma Biejia Decoction Inhibits Cell Growth in Multiple Myeloma by Inducing Autophagy-Mediated Apoptosis Through the ERK/mTOR Pathway - Dai, Huibo; Ma, Bangyun; Dai, Xingbin; Pang, Jie; Wang, Jingyu; Zhao, Yandong; Wang, Mengya; Zhang, Hong; Gao, Haoran; Qian, Shushu; Tian, Fang; Sun, Xuemei (Frontiers in Pharmacology, 2021)
Shengma Biejia decoction (SMBJD), a traditional Chinese formula recorded in Golden Chamber, has been widely used for the treatment of malignant tumors. However, its underlying molecular targets and mechanisms are still unclear. This study showed that SMBJD inhibited tumor growth and stimulated hemogram recovery significantly in a multiple myeloma xenograft model. Western blot and immunohistochemistry assays of tumor tissues showed that SMBJD reduced the ratio of autophagy-related proteins LC3-II/LC3-I, while P62 and apoptosis-related proteins cleaved caspase-3/caspase-3 and Bax/Bcl-2 were upregulated. In vitro experiments demonstrated the time-dependent and dose-dependent cytotoxicity of SMBJD on multiple myeloma cell lines H929 and U266 through MTT assays. The LC3-II/LC3-I ratio and number of GFP-LC3 puncta showed that SMBJD inhibited the autophagy process of H929 and U266 cells. Moreover, both SMBJD and 3-methyladenine (3-MA) caused a decrease in LC3-II/LC3-I, and SMBJD could not reverse the upregulation of LC3-II/LC3-I caused by bafilomycin A1 (Baf-A1). Furthermore, the results of annexin V-FITC and propidium iodide double staining demonstrated that SMBJD treatment induced apoptosis of H929 and U266 cells. These data prove that SMBJD inhibits autophagy and promotes apoptosis in H929 and U266 cells. The results also show that rapamycin could reduce the rate of SMBJD-induced apoptosis in H929 and U266 cells, at a concentration which had no effect on apoptosis but activated autophagy. In addition, analysis of the mechanism indicated that levels of phosphorylated ERK and phosphorylated mTOR were increased by treatment with SMBJD in vivo and in vitro. These results indicate that SMBJD, an old and effective herbal compound, could inhibit the viability of H929 and U266 cells and induce autophagy-mediated apoptosis through the ERK/mTOR pathway. Thus, it represents a potential therapy strategy for multiple myeloma.